INTERACTION EFFECTS OF SEASONS AND FARMING PRACTICES ON CORRELATION AND PATH ANALYSIS OF YIELD OF CUCUMBER (Cucumis sativus L.) - T. A. Sanni, M. A. Murtadha (Journal of Ecobiotechnology, 2018)
Association among yield characters is a pre-requisite for rapid crop improvement. A study was conducted to determine the effect of seasons and stake on correlation and path effects of cucumber yield traits. The experiment comprised of 2 seasons (wet and dry), 2 practices (staked and unstaked), six cucumber varieties replicated three times in a Randomized Complete Block Design (RCBD). Planting distance was 75×75 cm. Insect pests, weeds, and fungi were controlled as recommended. Data collected were subjected to correlation and path effect analysis. In the dry season, the two practices revealed highly significant genotypic correlation (P<0.05) between fruit yield and vine length (rg= 1.20 and 1.07) and phenotypic (rp=0.69 and 0.74). With days to flowering, fruit yield displayed highly significant genotypic (rg=-1.14 and -1.03) and phenotypic correlation (rg=-0.74 and -0.76). In the wet season, the two practices revealed highly significant positive genotypic (rg=0.95 and 0.84) and phenotypic correlation (rg=0.84 and 0.71) between fruit yield and fruit length. Path analysis showed that high yield was achieved in the dry season through the maximum effect of fruit girth 0.34 and 1.15 in the two practices and shorter days to flowering -0.39. In the wet season, maximum fruit yield was obtained through fruit length (5.86 and 0.28) in both practices, in addition to less fruit girth (-6.76) and short days to flowering (-0.67). In selection for high yields, the characters; vine length; fruit girth, fruit length and days to flowering can be utilized.